POLLUTION LEVEL IN RANU KLAKAH, LUMAJANG, EAST JAVA - Amrillah, Attabik Mukhammad; Salamah, Lutfi Ni`Matus; Amin, Abd. Aziz; Setyoningrum, Desy (Directorate of Research and Community Service (DRPM), 2024)
The increase in population, tourist activities and fish farming with floating net cages, whose waste is thrown directly into the Ranu Klakah, lead to pollution. The aim of this study is to determine the level of pollution in the ecosystem of Ranu Klakah Lake. The research method is descriptive. Water samples were collected at 3 stations, between 09.00 and 13.00 WIB. Measured water quality parameters: Temperature, TSS, DO, pH, ammonia, orthophosphate, nitrite, nitrate, BOD, COD. The analysis results were compared with the Water Quality Standard No. II as stipulated in the Regulation of the Government of the Republic of Indonesia No. 82 of 2001, which relates to water quality management and pollution control. Analysis of pollution level using the Storet method. According to the research results, there are two stations that have a moderate level of pollution. The data confirms that the waters of Ranu Klakah are generally moderately polluted. Community activities in fish farming, tourism and waste disposal contribute to the state of water pollution in Ranu Klakah. It is hoped that the results of this study will provide the relevant stakeholders with initial information for structuring the Ranu Klakah area